STUDY OF THE ORGANIZATIONAL LEARNING CULTURE OF AN EXCELLENT SCHOOL IN YONGZHOU, CHINA - YUAN, AILAN; CHAYANUVAT, ANCHALEE (Scholar: Human Sciences, 2022)
This research aimed to study excellent schools' organizational learning culture in Yongzhou, China. It adopted a mixed methods approach, collecting both quantitative as well as qualitative data. The quantitative data were gathered from a sample group of 439 teachers from the school who filled out the 39-item questionnaires, while the qualitative data were from in-depth interviews with the three school principals. Quantitative data were analyzed by factor analysis employing both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Qualitative data were analyzed by content analysis for emerging themes. The findings revealed from the questionnaire data analysis identified five aspects that shaped the organizational learning culture: learning strategies to adapt to changes, sharing vision, establishing a cooperative culture, encouraging innovation, and team learning. From the principals' interviews, four factors emerged. They were similar to those found in factor analyzing the quantitative data except for sharing vision. This could be explained that the principals may have believed that sharing vision was not highly significant for the schools because, as leaders of the schools, it was their responsibility, not the teachers', to participate in planning for the schools.